ADOPSI TEKNOLOGI PENGELOLAAN PAKAN TERNAKA CAJANUS CAJAN BERNUTRISI TINGGI SEBAGAI STRATEGI PEMBERDAYAAN EKONOMI PETERNAK - Dian Agustina; Iskandar Zainuddin Rela; Yoenita Jayadisastra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
Feed is the largest cost component in smallholder livestock farming, accounting for more than 70% of total production expenses. Therefore, efforts to improve efficiency through the utilization of locally available, high-nutrient feed materials have become a key strategy to enhance farmers' welfare. Cajanus cajan (pigeon pea) is one of the promising tropical forages that can serve as a substitute for concentrate feed due to its high crude protein content, ease of cultivation, and potential to reduce methane emissions. This study aims to examine the contribution of adopting Cajanus cajan-based feed processing technology to livestock productivity and the economic empowerment of small-scale farmers. The research employed Focus Group Discussions (FGDs) and structured interviews. The findings indicate that Cajanus cajan leaves can be effectively adopted by farmers, supporting self-sufficiency in feed production and reducing costs by up to 30%. From a socio-economic perspective, the adoption of this technology contributes to increased income, strengthens farmer group capacities, and promotes the development of markets for livestock products based on natural forages. While awareness and interest levels among farmers reached approximately 95%, the rate of sustained adoption remains below 40%, indicating the need for institutional support and ongoing training. Thus, the adoption of Cajanus cajan feed technology is not only technically and economically relevant but also aligns with the broader agenda of sustainable tropical livestock development. These findings demonstrate that the use of local resources can serve as an effective solution to the high cost of commercial feed. Furthermore, enhancing farmers’ knowledge and skills in feed processing is crucial to ensure the successful implementation of this innovation.